Capillary and venous malformation associated with skin hypotrophy. - Berti, I.; Dalmonte, P.; Cutrone, M.; Arcangeli, F.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
A 2-year-old girl was first observed due to angiomatous lesions of the left parietal region and neck, which were present since birth. Her mother told us a very precise history, documented by photos. The lesions were present since birth, their distribution and extent did not change with time and there was not a growing phase. On physical examination the little girl presented on her left frontal and parietal region and on the neck angiomatous lesions. The latter were confluent upon the ear. Three isolated, 3 cm in size lesions were located on the neck under the ear. Two smaller, isolated lesions were located on the left parietal region behind the largest confluent patch and finally a few mm in size angiomatous lesions were located on the rear surface of the left helix and preauricular region. The larger lesions were characterized by a peripheral barely raised border and by a whitish, atrophic center crossed by the hairs (Fig. 4). The photos given by her mother confirmed that distribution and extent of the lesions did not change with time and showed that the lesions at birth were uniformly red colored (Fig. 1, 2) and that after the first year turned into atrophic white lesions in the center (Fig. 3). With time atrophy got progressively more evident and extended towards the periphery, where a red, 6-8 mm in size border still persisted. The patient was observed by pediatricians, dermatologists, pediatric dermatologists and vascular surgeons, their diagnosis ranging between hemangioma and capillary malformation. Color Doppler ultrasonography performed in the IRCCS Giannina Gaslini Institute did not remove the doubt between hemangioma and capillary and venous malformation. Brain MRI did not show pathological findings. In the same department an isolated lesion of the neck was removed and the histological examination showed capillaries and venules in the dermis and subcutaneous fat tissue, leading to the final diagnosis of vascular malformation of venous capillary type. A careful observation of the histological sections showed in the middle of the lesion a thinned dermis with decreased number of vessels and an almost rectlineal dermal epidermal junction. These findings were consistent with the clinical atrophic appearance of the superficial skin.